EMOTIONAL CHALLENGES OF JUNIOR SECONDARY STUDENTS: IMPLICATIONS FOR SCHOOL GUIDANCE AND COUNSELLING - Putra, Nurul Ainulhaq Tiara; Suprihatiningrum, Jamil; Nurbaeti, Nurbaeti (UIN Sumatera Utara Medan, 2026)
Early adolescence represents a critical developmental period marked by rapid biological, psychological, and social changes that significantly influence emotional functioning. This study aims to explore the dynamics of emotional development among junior secondary school students and to identify the internal and external factors shaping these dynamics within a specific school context. Employing a qualitative case study design, this research was conducted at a public junior secondary school in Gowa Regency, Indonesia. Data were collected through participant observation, semi-structured in-depth interviews with students, guidance and counseling teachers, homeroom teachers, and parents, as well as document analysis. Thematic analysis was applied using an interactive data analysis model and interpreted through Erikson’s psychosocial development framework. The findings reveal that students experience highly fluctuating emotional states characterized by impulsivity, emotional reactivity, and difficulties in self-regulation. Internally, emotional instability is strongly associated with identity confusion and limited emotion regulation skills. Externally, insufficient family emotional support and challenging peer interactions further exacerbate students’ emotional vulnerability. Although guidance and counseling services are available, emotional support practices remain largely reactive rather than preventive. This study contributes to the global literature by providing a contextualized understanding of adolescent emotional development in a Global South public school setting, highlighting the importance of holistic, school-based emotional support systems that integrate counseling, pedagogy, and family involvement.